2019
DOI: 10.3390/ma12244082
|View full text |Cite
|
Sign up to set email alerts
|

General Study and Gene Expression Profiling of Endotheliocytes Cultivated on Electrospun Materials

Abstract: Endothelization of the luminal surface of vascular grafts is required for their long-term functioning. Here, we have cultivated human endothelial cells (HUVEC) on different 3D matrices to assess cell proliferation, gene expression and select the best substrate for endothelization. 3D matrices were produced by electrospinning from solutions of poly(D,L-lactide-co-glycolide) (PLGA), polycaprolactone (PCL), and blends of PCL with gelatin (Gl) in hexafluoroisopropanol. Structure and surface properties of 3D matric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…The viability of human vascular endothelial cells cultured on biodegradable polymer poly(l-lactic acid) scaffolds was 50% lower compared to cells cultivated in TCPS [ 33 ]. The adhesion and proliferation of HUVEC cells on PLGA scaffolds was 30–40% [ 34 ]. According to our data, PCL-based ACN-enriched scaffolds have demonstrated good biocompatibility in comparison with others materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The viability of human vascular endothelial cells cultured on biodegradable polymer poly(l-lactic acid) scaffolds was 50% lower compared to cells cultivated in TCPS [ 33 ]. The adhesion and proliferation of HUVEC cells on PLGA scaffolds was 30–40% [ 34 ]. According to our data, PCL-based ACN-enriched scaffolds have demonstrated good biocompatibility in comparison with others materials.…”
Section: Resultsmentioning
confidence: 99%
“…Gingival fibroblasts (GFs) obtained from human gingiva, as described in [ 37 ], were kindly gifted by Dr. Cherepanova. Human umbilical vein endothelial cells (HUVECs) were isolated and cultivated, as described previously [ 34 , 38 ]. Cells were cultured in IMDM (Invitrogen, Carlsbad, CA, USA) medium supplemented with 10% fetal bovine serum (FBS, Gibco, USA) and 100 units of streptavidin/penicillin in a CO 2 incubator at 37 °C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Since silicates readily bind to DNA and are widely used for DNA isolation [39][40][41], we used silica NPs as pDNA carriers for the production of long-term pDNA-releasing scaffolds. To produce these scaffolds, we used polycaprolactone as a basic polymer combined with 10% gelatin, in order to increase cell adhesion [56]. Previously, we demonstrated that drug-enriched PCL-based scaffolds are well suited for vascular stent coatings, demonstrating satisfactory mechanical properties and biphasic long-term drug delivery [57,58].…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, nano-fiber technology advances permit the fabrication of nano-fibers from a wide range of materials including natural and synthetic polymers [200][201][202][203][204][205][206][207][208][209][210][211][212][213], ceramics, metals, as well as inorganic/inorganic or organic/inorganic composite systems [214][215][216][217][218][219][220]. A unique combination of properties such as the conductivity of metallic dopants accompanied by the flexibility of polymers can be obtained by a combination of various materials.…”
Section: Summary and Future Road Mapsmentioning
confidence: 99%